Analisis Perbandingan Kinerja Keuangan pada PT Mayora Indah Tbk dengan PT Garudafood Putra Putri Jaya Tbk - Nursinah; Wulandari; Alwi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2025)
This study aims to analyze and compare the financial performance of PT Mayora Indah Tbk and PT Garudafood Putra Putri Jaya Tbk for the period 2019–2024 based on profitability and solvency ratios. The research employs a quantitative approach with a comparative method. Secondary data were obtained from the annual financial statements of both companies and analyzed using SPSS version 26.0. The examined ratios include Return on Assets (ROA), Return on Equity (ROE), Debt to Asset Ratio (DAR), and Debt to Equity Ratio (DER). The results reveal a significant difference in ROA, where PT Mayora Indah Tbk has a higher average ROA compared to PT Garudafood, indicating better asset management efficiency by Mayora. No significant difference is found in ROE, suggesting that both companies have relatively similar capabilities in utilizing equity to generate profits. However, significant differences are identified in DAR and DER, with PT Garudafood showing a higher reliance on debt financing than PT Mayora. Overall, PT Mayora Indah Tbk demonstrates more stable and efficient financial performance, while PT Garudafood needs to enhance asset management effectiveness and reduce dependency on debt. The findings of this study are expected to provide valuable insights for investors and company management in formulating appropriate financial strategies.